A new species, Yalvaciana unal sp. nov. of the genus Yalvaciana Ciplak et al. 2002 (Orthoptera: Tettigoniidae: Tettigoniinae) from Kashmir, Jammu and Kashmir, India - Shah, Muzamil Syed; Usmani, Mohd Kamil (Zootaxa, 2022)
A new bushcricket species, Yalvaciana unal sp. nov. of the genus Yalvaciana Ciplak et al. (2002) is described. It is distinguished from other species of the genus based on various morphological characters. The genus has two species, Yalvaciana yalvaci Demirsoy, (1974) endemic to Anatolia, Turkey Taylan et al. (2019) and Yalvaciana allowpora Shah & Usmani, (2021). Detailed information about the morphology and distribution of the new species is given. The holotype has been deposited in the museum of the Zoology Department, Aligarh Muslim University, Aligarh, India.